Helminthic parasites of chickens (Gallus domesticus) in different regions of São Paulo State, Brazil - da Silva, Giane Serafim; Romera, D. M.; Fonseca, L. E.C. [UNESP]; Meireles, M. V. [UNESP] (FapUNIFESP (SciELO), 2016)
The Brazilian poultry industry is an outstanding national and international agribusiness sector. Among the Brazilian states, São Paulo is the largest producer of commercial eggs and the fourth largest producer and exporter of chicken meat. Alternatively, semiintensive and/or organic poultry production have also obtained a significant share of the domestic market as a result of consumer demand. Helminths affect the performance of the birds, causing significant direct or indirect losses. The objective of the present study was to identify the main helminth species present in chickens reared in 17 municipalities of the state of São Paulo. In total, 359 adult birds were investigated. The birds were reared in different housing systems and were obtained from 69 farms in the selected regions. The birds were submitted to procedures for the detection and identification of helminth parasites, following international standards. The evaluation of the small intestine employed the Mello-Campos method (Mello & Campos, 1974), which allows better recovery of cestode scolices attached to the intestinal mucosa. Stereomicroscopy was used to evaluate the collected materials, and light microscopy was used to identify the species based on their morphological characteristics. The following helminth species were diagnosed in chickens reared in 17 municipalities of the state of São Paulo: nematodes (Ascaridia galli, Capillaria sp., Cheilospirura hamulosa, Heterakis gallinarum, Oxyspirura mansoni, and Strongyloides sp.), cestodes (Amoebotaenia cuneata, Choanotaenia infundibulum, Hymenolepis sp., Raillietina cesticillus, Raillietina echinobothrida, and Raillietina tetragona), and trematodes (Zygocotyle lunata and Postharmostomum commutatum).
Keywords: Cestodes; Chicken; Helminths; Nematodes; Trematodes